Pelagic Iron Recycling in the Southern Ocean: Exploring the Contribution of Marine Animals - Ratnarajah, Lavenia; Nicol, Steve; Bowie, Andrew R. (Frontiers in Marine Science, 2018)
The availability of iron controls primary productivity in large areas of the Southern Ocean. Iron is largely supplied via atmospheric dust deposition, melting ice, the weathering of shelf sediments, upwelling, sediment resuspension, mixing (deep water, biogenic and vertical mixing) and hydrothermal vents with varying degrees of temporal and spatial importance. However, large areas of the Southern Ocean are remote from these sources, leading to regions of low primary productivity. Recent studies suggest that recycling of iron by animals in the surface layer could enhance primary productivity in the Southern Ocean. The aim of this review is to provide a quantitative and qualitative assessment of the current literature on pelagic iron recycling by marine animals in the Southern Ocean and highlight the next steps forward in quantifying the retention and recycling of iron by higher trophic levels in the Southern Ocean. Phytoplankton utilise the iron in seawater to meet their metabolic demand. Through grazing, pelagic herbivores transfer the iron in phytoplankton cells into their body tissues and organs. Herbivores can recycle iron through inefficient feeding behaviour that release iron into the water before ingestion, and through the release of faecal pellets. The iron stored within herbivores is transferred to higher trophic levels when they are consumed. When predators consume iron beyond their metabolic demand it is either excreted or defecated. Waste products from pelagic vertebrates can thus contain high concentrations of iron which may be in a form that is available to phytoplankton. Bioavailability of faecal iron for phytoplankton growth is influenced by a combination of the size of the faecal particle, presence of organic ligands, the oxidation state of the iron, as well as biological (e.g. remineralisation, coprochaly, coprorhexy and coprophagy) and physical (e.g. dissolution, fragmentation) processes that lead to the degradation and release of faecal iron. The flux of dissolved iron from pelagic recycling is comparable to other sources in the region such as atmospheric dust, vertical diffusivity, vertical flux, lateral flux and upwelling, but lower than sea ice, icebergs, sediment resuspension, and deep winter mixing. The temporal and seasonal importance of these various factors requires further examination.